BEER analysis of Kepler and CoRoT light curves – V. eBEER: extension of the algorithm to eccentric binaries. Issue 4 (6th August 2020) - Engel, M; Faigler, S; Shahaf, S; Mazeh, T
ABSTRACT: We present an extension of the BEER model for eccentric binaries – eBEER, approximating the BEaming, Ellipsoidal, and Reflection effects by harmonic series of the Keplerian elements of their orbit. As such, it can be a tool for fast processing of light curves for detecting non-eclipsing eccentric binary systems. To validate the applicability of the eccentric model and its approximations, we applied eBEER to the Kepler light curves, identified a sample of bright non-eclipsing binary candidates, and followed three of them with the Wise observatory eShel spectrograph. After confirming the three systems are indeed radial velocity (RV) binaries, we fitted the light curves and the RV data with PHOEBE, a detailed numerical light curve and RV model, and showed that the PHOEBE derived parameters are similar to those obtained by the eBEER approximation.